(untitled) (Research, Society and Development, 2025)
Introduction: Alzheimer’s disease (AD) is a neurodegenerative disorder that leads to progressive loss of memory and cognitive functions. With the aging of the population, the prevalence of AD has increased significantly. Genetic factors and imbalance in brain metabolism contribute to the pathogenesis of AD. Objective: To analyze the most recent scientific evidence on the clinical use of THC and CBD in the treatment of AD, including the impact of these compounds on symptoms, disease progression, and quality of life of patients. Methodology: Integrative literature review carried out in the PubMed database, between 2015 and 2025, using the descriptors "THC", "Cannabidiol" and "Alzheimer’s disease", combined by the Boolean operator "AND". Five articles were selected for analysis, based on their relevance and coherence with the proposed theme. Results and Discussion: The review found that both THC and CBD have therapeutic potential to alleviate AD symptoms, such as agitation, aggression, apathy, and sleep disturbances. Preclinical and clinical studies suggest that THC may reduce impulsivity and agitation, while CBD, with its anti-inflammatory and antioxidant properties, may have neuroprotective effects. The combination of THC and CBD has shown promising results in improving memory and reducing β-amyloid plaque deposition in animal models. However, most studies have limitations, such as small sample sizes, lack of standardization in dosages, and absence of double-blind randomized clinical trials. Conclusion: The results indicate that THC and CBD may be useful in treating AD symptoms, but more research is needed to determine optimal dosages, evaluate long-term effects, and ensure patient safety. Personalized treatments and ongoing follow-up are essential for the success of therapy.